Summer habitat associations of bats between riparian landscapes and within riparian areas ... - Lundy, Mathieu; Montgomery, Ian (Zenodo, 2010)
(Uploaded by Plazi for the Bat Literature Project) The present study examines those features which promote bat feeding in agricultural riparian areas and the riparian habitat associations of individual species. Activity of Nathusius' pipistrelle (Pipistrellus nathusii), common pipistrelle (Pipistrellus pipistrellus), soprano pipistrelle (Pipistrellus pygmaeus), Leisler's bat (Nyctalus leisleri), and Myotis species (Myotis sp.) were recorded, and their habitat associations both "between" and "within" riparian areas were analyzed. General feeding activity was associated with reduced agricultural intensity, riparian hedgerow provision, and habitat diversity. Significant habitat associations for P. pipistrellus were observed only within riparian areas. Myotis species and P. pygmaeus were significantly related to indices of landscape structure and riparian hedgerow across spatial scales. Myotis species were also related to lower levels of riffle flow at both scales of analysis. The importance of these variables ...